Spy x family. 11 - Endō, Tatsuya, 1980- (VIZ Media, LLC, 2024)
"Threatened by Yor's relationship with Melinda Desmond, Anya gets serious about her own friendship scheme. On the way to a museum field trip, however, she and her class become the target of activists looking to free their political allies . . ."--Back cover.